PERHITUNGAN DATA EPHEMERIS KOORDINAT MATAHARI MENGGUNAKAN ALGORITMA JEAN MEEUS HIGHER ACCURACY DAN KETERKAITANNYA DENGAN PENGEMBANGAN ILMU FALAK - reza akbar (Universitas Islam Negeri Ar-Raniry, 2017)
Data of solar coordinate such as longitude and latitude of the ecliptic, declination, and right ascension are the data that are often involved in astronomical reckoning and practical islamic astronomy. These data are often found in ephemeris tables such as the ephemeris of Hisab Rukyat by Ministry of Religious Affairs of the Republic of Indonesia, Nautica Almanac and others. One of the algorithms used in the preparation of ephemeris data tables is the Jean Meeus Higher Accuracy algorithm. Calculation of ephemeris data of solar coordinates using these algorithms starts with counting Julian Day (JD) and Julian Day Ephemeris (JDE). By using advanced algorithms based on VSOP87 theory, we can then calculate the longitude and latitude of the solar ecliptic, the distance of the earth to the Sun, the true obliquity (angle between the celestial equator and the ecliptic), the right ascension and declination, the equation of time and the Sun's semi diameter. The calculation of the solar coordinate in this paper is for June 7, 2017 at 19.00 WIB or 12.00 GMT. The results will then be compared with the data of solar coordinate in Ephemeris Hisab Rukyat 2017 at the same time.